Mouse soup - Lobel, Arnold (New York : HarperCollins, 1977)
A mouse convinces a weasel he needs the ingredients from several stories to make a tasty mouse soup.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
2.2.
2.2
K-3
Keywords: Mice -- Fiction; Mice -- Fiction; Readers (Elementary).